(untitled) (New Jersey, 2002)
The International Conference on Calorimetry in Particle Physics is the major forum for the state-of-the-art developments of calorimetry technologies. The Tenth Conference was attended by more than 150 physicists from 16 countries and covered all aspects of calorimetric particle detection and measurements, with emphasis on high energy physics and astrophysics experiments. The proceedings contain three parts: introductory papers, contributed papers and perspective papers. The introduction starts with a historical review of calorimetry developments, and continues with overviews of the current status of calorimetry in high energy physics and astrophysics, which are followed by discussions on calorimetry in future accelerator facilities, such as linear colliders and the Super B factories. A "hot" technology regarding the "energy flow concept" is also discussed. The contributed papers are organized in 11 sessions. The perspective papers summarize the physics and limitation of calorimeter applications in high energy physics, astrophysics and medical industries.
Keywords: Calorimetry,Particles ( nuclear physics ),Phép đo nhiệt lượng,Phân tử ( vật lý nguyên tử ); Technique